A Study on the Factors Responsible For Dowry System and Its Impact on Indian Society: An in-depth analysis of the dowry system and its impact on women in Indian society (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Today, Indian society is surrounded with many problemssuch as unemployment, illiteracy, population growth, terrorism etc.  Among these problems, a problem which is deeprooted in Indian Society is the problem of dowry system. It has become theeveryday news item, no day passes away when we don’t hear news relating todowry death or dowry harassment. The irony lies in the fact that the women inIndia are worshipped in the form of Shakti; she is burned and harassed by herin-laws every day in one part of the nation or the other. Dowry refers tomoney, gifts, goods or estate that wife brings to her husband in marriage.